Microstories and presentations (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. How can you use storytelling in your everyday life? In this track, you'll learn about three different types of micro-story. We'll tell you how to structure stories about the past, the present and the future. Your tales will be so good that people will want to repeat them. Learning Objectives Learn why stories connect you with your audience Learn how to construct three types of micro-story Learn tips on presenting your micro-stories.